The effect of electronic word of mouth, brand image and trust on online purchase intention through social media - Tri Tata Wilia; Gesit Thabrani (Marketing Management Studies, 2023)
This study aims to analyze the effect of electronic word of mouth, brand image and trust on online purchase intention through social media for Solok City consumers. The population of this research is consumers has shopped through media. The number of this research is 189 respondents. Data collected by distributing questionnaires online processing data is carried out using the SmartPLS software. The results of this study indicate that (1) eWOM has a significant effect and positive on Trust, (2) eWOM has a significant effect and positive on Brand Image, (3) Trust has a significant effect and positive on Online Purchase Intention, (4) Brand Image has a significant effect and positive on Online Purchase Intention, (5) eWOM has no significant effect on Online Purchase Intention, (6) Brand Image has a significant effect and positive on Trust, (7) eWOM has a significant effect and positive on Online Purchase Intention with Trust as mediation, (8) eWOM has a positive and significant effect on Online Purchase Intention with Brand Image as mediation, (9) Brand Image has a positive and significant effect on Online Purchase Intention with Trust as mediation